Global, regional and country burden of high BMI-related liver cancer among individuals aged above 70: trends from 1990 to 2021 and projections to 2044 - He, Ke-Jie; Shu, Wanyi; Hong, Yanggang (Frontiers in Public Health, 2025)
BackgroundLiver cancer (LC) is a major global health concern, being the fourth leading cause of cancer-related mortality. Older adults are more susceptible, though mortality rates for those over 70 are declining. However, disability from non-communicable diseases remains high. High body mass index (BMI) is a notable risk factor for LC, with high BMI-related liver cancer (HB-LC) being a major concern.MethodsThis study utilized Global Burden of Disease (GBD) 2021 dataset to assess the impact of HB-LC on individuals aged 70 and older from 1990 to 2021, with forecasts extending to 2044. Disease burden across socio-demographic index (SDI) regions was evaluated using age-standardized disability-adjusted life years (DALYs). Joinpoint regression and age-period-cohort models were used to analyze DALY trends and demographic influences, and decomposition analysis assessed the effects of population aging, growth, and epidemiological shifts.ResultsOur findings revealed significant geographical disparities in HB-LC mortality, with East Asia, Southeast Asia, and parts of West Africa showing the highest rates. Global HB-LC DALYs increased by 2.49% annually, with low SDI regions experiencing recent acceleration. Gender disparity persisted, with males facing a steeper rise in HB-LC burden. Age-related DALY rates peaked in the 80–89 age groups, showing complex patterns across SDI regions. Epidemiological changes primarily drove the increased HB-LC burden in high SDI regions, while population growth was more significant in low SDI regions.ConclusionThis data analysis underscores necessity for region-specific public health strategies and demographic-focused interventions, enhancing surveillance and targeting efforts to mitigate the increasing burden of HB-LC among the older adults.